VO2@PHFBMA-b-PDMA nanoparticles and preparation method and application thereof

By preparing VO2@PHFBMA-b-PDMA nanoparticles, the problem of insufficient stability and dispersion of VO2 powder is solved, high stability and excellent dispersion are achieved, and its application performance in intelligent thermal insulation coatings is improved. .

CN116970302BActive Publication Date: 2025-02-11UNIV OF JINAN
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310972807.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-08-03
Publication Date
2025-02-11
Estimated Expiration
2043-08-03

AI Technical Summary

Technical Problem

In the prior art, VO2 powder is easily oxidized under the action of water and oxygen in the air, resulting in poor stability and insufficient dispersion and weather resistance in aqueous emulsions, which affects its application.

Method used

By preparing VO2@PHFBMA-b-PDMA nanoparticles, the high stability and hydrophobicity of the internal fluoropolymer PHFBMA are utilized, and combined with the external hydrophilic shell PDMA, the weather resistance and dispersion of VO2 powder in aqueous resin are improved.

Benefits of technology

It realizes high stability, excellent dispersion and near-infrared dimming performance of VO2 powder, and improves its application performance in intelligent thermal insulation coatings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116970302B_ABST
    Figure CN116970302B_ABST
Patent Text Reader

Abstract

The present invention provides a VO2@PHFBMA‑b‑PDMA nanoparticle, a preparation method and an application thereof, and belongs to the field of functional composite materials. The particle size of the VO2@PHFBMA‑b‑PDMA nanoparticle is 30 to 40 nm, and the preparation method comprises: (1) preparation of vanadium dioxide powder; (2) preparation of thiol-terminated PDMA‑b‑PHFBMA‑SH amphiphilic block polymer; (3) preparation of VO2@PHFBMA‑b‑PDMA nanoparticles. The VO2@PHFBMA‑b‑PDMA nanoparticles prepared by the VO2@PHFBMA‑b‑PDMA nanoparticles provided by the present invention have excellent stability, dispersibility and near-infrared dimming performance, and have great advantages in the application in the coating field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of functional composite materials, and specifically relates to a VO 2 @PHFBMA-b-PDMA nanoparticles, preparation methods and applications. Background Art

[0002] Vanadium dioxide (VO 2 ) is a thermochromic material that can undergo phase change at 68°C. It has the characteristic of different infrared light reflectivity before and after the phase change. It can be used as a coating material to intelligently control the transmittance of near-infrared light in building doors and windows, thereby intelligently controlling indoor temperature, reducing the use of indoor air conditioning and cooling in high temperature environments, and reducing energy consumption, which is conducive to energy conservation and emission reduction. However, in actual applications, VO 2 It is easily oxidized to vanadium pentoxide (V 2 O 5 ), its poor stability limits its practical application. 2 The strategy for powder stability is to modify the surface and construct a core-shell structure for VO 2 Nanopowders are coated, and shell materials form a dense protective layer on the surface of the powders. Common shell materials are mainly divided into small organic molecules (silane coupling agents), inorganic oxides (silicon dioxide, titanium dioxide, etc.) and organic polymers (such as polydopamine, polystyrene, etc.). Although the above method of improving the stability of vanadium dioxide can improve the weather resistance of vanadium dioxide powder to a certain extent, the commonly used shell materials are all inorganic materials or hydrophobic organic materials, and the inorganic shell materials cannot solve the dispersibility of the powder in the aqueous emulsion at the same time. The shell materials of non-fluorine-containing polymers are easily decomposed under sunlight and cannot meet the long-term application requirements of powders and coatings. Summary of the invention

[0003] The object of the present invention is to provide a VO 2 @PHFBMA-b-PDMA nanoparticles, preparation methods and applications are used to solve the problems of poor powder dispersibility, poor stability and poor dimming performance existing in the prior art.

[0004] In order to achieve the above purpose or other purposes, the present invention is implemented through the following technical solutions.

[0005] A VO 2 @PHFBMA-b-PDMA nanoparticles, the VO 2 @The particle size of PHFBMA-b-PDMA nanoparticles is 30-40 nm.

[0006] Preparation of VO 2The method of @PHFBMA-b-PDMA nanoparticles comprises the following steps:

[0007] (1) Preparation of vanadium dioxide powder; (2) Preparation of thiol-terminated PDMA-b-PHFBMA-SH amphiphilic block polymer; (3) VO 2 @PHFBMA-b-PDMA nanoparticles preparation.

[0008] Specifically, the steps include:

[0009] (1) Preparation of vanadium dioxide powder:

[0010] V 2 O 5 Add to deionized water, stir to form a dispersion, heat the dispersion and drop hydrazine hydrate under stirring, continue stirring to react after the dropwise addition is completed, then transfer the solution to a reactor to continue the reaction, perform post-treatment after the reaction is completed, and obtain vanadium dioxide powder;

[0011] (2) Preparation of thiol-terminated PDMA-b-PHFBMA-SH amphiphilic block polymer:

[0012] a) adding N,N-dimethylacrylamide, S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) and azobisisobutyronitrile to 1,4-dioxane solvent, stirring and reacting under nitrogen protection after being completely dissolved, precipitating and washing the resulting solution in n-hexane after the reaction, and filtering the resulting product under vacuum drying at 30-60° C. for 8-24 h to obtain trithioester-terminated poly(N,N-dimethylacrylamide), which is recorded as PDMA-DOPAT;

[0013] b) adding the PDMA-DOPAT, hexafluorobutyl methacrylate and azobisisobutyronitrile prepared in step a) into tetrahydrofuran, stirring until completely dissolved, stirring and reacting under nitrogen protection, and after the reaction, dropping the solution into n-hexane for precipitation and washing, filtering and collecting the precipitate, and vacuum drying at 30-60° C. for 8-24 h to obtain poly(N,N-dimethylacrylamide-b-hexafluorobutyl methacrylate), recorded as PDMA-b-PHFBMA-DOPAT;

[0014] c) adding the PDMA-b-PHFBMA-DOPAT, n-hexylamine and tributylphosphine prepared in step b) into tetrahydrofuran, stirring and reacting under nitrogen protection, adding the reaction solution into n-hexane for precipitation and washing to obtain a solid product after the reaction is completed, and vacuum drying at 30-60° C. for 8-24 hours to obtain a thiol-terminated PDMA-b-PHFBMA-SH amphiphilic block polymer;

[0015] (3) VO 2Preparation of @PHFBMA-b-PDMA nanoparticles:

[0016] a) ultrasonically dispersing the vanadium dioxide powder prepared in step (1) in anhydrous ethanol, adding ammonia water to adjust the pH, adding γ-(methacryloyloxy)propyltrimethoxysilane, and then heating the system for reaction. After the reaction, centrifuging, washing with anhydrous ethanol, and vacuum drying at 30-60° C. for 12-24 h to obtain VO 2 @KH-570 nano powder;

[0017] b) Change VO 2 @KH-570 nano powder is dispersed in tetrahydrofuran, and then the PDMA-b-PHFBMA-SH amphiphilic block polymer prepared in step (2) is added and stirred until fully dissolved, and then the initiator AIBN is added, and then reacted under nitrogen protection. After the reaction is completed, centrifugation and tetrahydrofuran washing are performed, and the washed product is vacuum dried at 30-60°C for 12-24h to obtain VO 2 @PHFBMA-b-PDMA nanoparticles.

[0018] Preferably, in step (1), V 2 O 5 The mass ratio to deionized water is (1-7):(60-160).

[0019] Preferably, in step (1), the dispersion is heated to 50-80° C. and then hydrazine hydrate is added dropwise under stirring.

[0020] Preferably, in step (1), V 2 O 5 The mass ratio of hydrazine hydrate to hydrazine hydrate is (5-10): (1-5).

[0021] Furthermore, the selected hydrazine hydrate is 40wt% hydrazine hydrate.

[0022] Further, in step (1), the hydrazine hydrate is added at a rate of 0.1 to 1 mL / min. Preferably, in step (1), the hydrazine hydrate is added at a rate of 0.1 to 1 mL / min.

[0023] Preferably, after the dropwise addition in step (1) is completed, the stirring reaction time is continued for 0.5 to 5 hours. Preferably, in step (1), the reaction temperature in the reactor is 220 to 350° C., and the reaction time is 6 to 32 hours.

[0024] Preferably, after the reaction in step (1) is completed, the post-treatment sequentially comprises centrifugation at a speed of 1000-8000 rpm for 10-30 min and vacuum drying at 30-60° C. for 8-24 h.

[0025] Preferably, in step (2), the mass ratio of N,N-dimethylacrylamide (DMA) and S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT) in a) is (80-120):(5-15).

[0026] Preferably, in step (2), the mass ratio of S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT) and azobisisobutyronitrile (AIBN) in a) is (15-50): (0.5-7).

[0027] Preferably, in step (2), the mass ratio of 1,4-dioxane to N,N-dimethylacrylamide in a) is (5-10):(0.5-5).

[0028] Preferably, in step (2), the stirring reaction temperature under nitrogen protection in a) is 55 to 70° C., and the reaction time is 12 to 24 h.

[0029] Preferably, in step (2), the mass ratio of PDMA-DOPAT, hexafluorobutyl methacrylate (HFBMA) and azobisisobutyronitrile (AIBN) in b) is (260-350): (150-240): (0.5-5).

[0030] Preferably, in step (2), the mass ratio of PDMA-DOPAT to tetrahydrofuran in b) is 1:(3-20).

[0031] Preferably, in step (2), the stirring reaction temperature under nitrogen protection in b) is 55 to 70° C., and the reaction time is 12 to 24 h.

[0032] Preferably, in step (2), the amount of n-hexane in processes a), b) and c) should be sufficient to ensure complete precipitation.

[0033] Preferably, in step (2), the mass ratio of PDMA-b-PHFBMA-DOPAT, n-hexylamine and tributylphosphine in c) is (250-450):(45-90):(2-12).

[0034] Preferably, in step (2), the mass ratio of PDMA-b-PHFBMA-DOPAT to tetrahydrofuran in c) is 1:(2-10).

[0035] Preferably, in step (2), the stirring reaction temperature under nitrogen protection in c) is 25 to 45° C., and the reaction time is 3 to 12 h.

[0036] Preferably, in step (3), the ultrasonic dispersion time in a) is 20 to 40 minutes.

[0037] Preferably, in step (3), the mass ratio of vanadium dioxide powder to anhydrous ethanol in a) is (0.1-4):(60-120).

[0038] Preferably, in step (3), aqueous ammonia is added dropwise in a) to adjust the pH to 8-12.

[0039] Preferably, in step (3), the mass ratio of the vanadium dioxide powder to γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) in a) is (5-30):(0.5-3).

[0040] Preferably, in step (3), the heating reaction temperature in a) is 50 to 70° C., and the reaction time is 3 to 12 h.

[0041] Preferably, in step (3), the unreacted KH-570 is removed by washing with anhydrous ethanol 3 to 5 times in a).

[0042] Preferably, in step (3), b) VO 2 @The mass ratio of KH-570 nano powder to tetrahydrofuran is (0.1~10):(60~120).

[0043] Preferably, in step (3), b) VO 2 @The mass ratio of KH-570 nano powder to AIBN is (20-50):1.

[0044] Preferably, in step (3), the reaction temperature under nitrogen protection in b) is 55-70° C., and the reaction time is 12-24 h.

[0045] Preferably, in step (3), the unreacted amphiphilic block polymer is removed by washing with THF 3 to 5 times in b).

[0046] The present invention also protects a method of using the above VO 2 Smart thermal insulation coating prepared with @PHFBMA-b-PDMA nanoparticles.

[0047] The preparation method of the intelligent thermal insulation coating is as follows: 2 The aqueous dispersion of @PHFBMA-b-PDMA nanoparticles is evenly added to the aqueous resin and stirred until uniformly dispersed to obtain a system dispersion; the film-forming aid, leveling agent and defoaming agent are evenly mixed, then added to the system dispersion and stirred evenly to obtain the smart thermal insulation coating.

[0048] Furthermore, waterborne resin and VO 2 The mass ratio of the aqueous dispersion of @PHFBMA-b-PDMA nanoparticles is (50-100): (40-60); VO 2The mass percentage of the aqueous dispersion of @PHFBMA-b-PDMA nanoparticles is 1wt%.

[0049] Furthermore, VO 2 The dripping speed of the aqueous dispersion of @PHFBMA-b-PDMA nanoparticles is 0.5-2 mL / min. Furthermore, the stirring rate during the dripping process is 4000-8000 rpm, and the stirring time after the dripping is completed is 0.5-5 h.

[0050] Furthermore, the water-based resin is selected from water-based polyurethane resin and water-based acrylate resin.

[0051] Furthermore, the mass ratio of the water-based resin, the film-forming aid, the leveling agent, and the defoaming agent is (50-100): (10-30): (0.5-5): (1-3).

[0052] Furthermore, the film-forming aid is selected from alcohol ether film-forming aids, the leveling agent is selected from silicone leveling agents, and the defoaming agent is selected from silicone resin defoaming agents.

[0053] The smart heat-insulating coating prepared by the present invention is evenly coated on the surface of an ordinary clean glass plate by a conventional roller coating method, and the wet film thickness after coating is 45 to 55 μm, thereby obtaining smart heat-insulating glass. Specifically, the smart heat-insulating coating is evenly coated on the surface of a clean glass plate by a roller coating method, and is placed in an oven at 60° C. to assist the accelerated curing of the coating, thereby obtaining vanadium dioxide-based smart heat-insulating glass.

[0054] The present invention provides a VO 2 @PHFBMA-b-PDMA nanoparticles are a double-shell vanadium dioxide-based hybrid material. The high stability and hydrophobicity of the internal fluorinated polymer PHFBMA are used to improve the weather resistance of vanadium dioxide powder in water-based resins, while the external hydrophilic shell PDMA can effectively improve the dispersibility of vanadium dioxide in water-based emulsions, prevent sedimentation and agglomeration, and at the same time, the interfacial hydrogen bonds between the shell material and the film-forming resin help improve the compatibility of the filler and the resin, reduce the interface structural defects inside the functional coating, and improve the weather resistance of the functional coating. The preparation method provided by the present invention has a certain universality, and the prepared VO 2 @PHFBMA-b-PDMA nanoparticles have excellent stability, dispersibility and near-infrared dimming properties, and have great advantages in the field of smart thermal insulation coatings.

[0055] The VO prepared by the present invention 2 The smart thermal insulation coating prepared with @PHFBMA-b-PDMA nanoparticles has excellent dimming properties and can achieve efficient thermal insulation effect. BRIEF DESCRIPTION OF THE DRAWINGS

[0056] Figure 1 Schematic diagram of the synthesis of the PDMA-b-PHFBMA-DOPAT block polymer prepared in Example 1;

[0057] Figure 2 This is the H NMR spectrum of the PDMA-b-PHFBMA-DOPAT block polymer prepared in Example 1;

[0058] Figure 3 The UV absorption spectra of PDMA-b-PHFBMA-DOPAT and PDMA-b-PHFBMA-SH prepared in Example 1;

[0059] Figure 4 VO prepared in Example 1 2 SEM image of powder;

[0060] Figure 5 VO prepared in Example 1 2 Powder, VO 2 @XRD pattern of PHFBMA-b-PDMA nanoparticles;

[0061] Figure 6 VO prepared in Example 1 2 Powder, VO 2 @KH-570, VO 2 @Thermogravimetric curve of PHFBMA-b-PDMA nanoparticles;

[0062] Figure 7 VO prepared in Example 1 2 Powder, VO 2 @KH-570 and VO 2 @PHFBMA-b-PDMA nanoparticles dispersion test results in water phase (from left to right: VO 2 Powder, VO 2 @PHFBMA-b-PDMA nanoparticles, VO 2 @KH-570);

[0063] Figure 8 VO prepared in Example 1 2 Powder, VO 2 @KH-570 and VO 2 @PHFBMA-b-PDMA nanoparticles acid resistance and antioxidant test results (from left to right: VO 2 Powder, VO 2 @KH-570, VO 2 @PHFBMA-b-PDMA nanoparticles);

[0064] Fig. 9 The actual pictures of the thermal insulation coatings prepared in Application Example 1, Application Example 2, and Application Example 3, as well as the UV-Vis-NIR transmission spectra at different temperatures, where (a) is VO 2 Based on smart thermal insulation coating, (b) VO 2 @KH570 based intelligent thermal insulation coating, (c)VO 2 @PHFBMA-b-PDMA-based smart thermal insulation coating, (d) is the UV-visible-near-infrared transmission spectrum at different temperatures. DETAILED DESCRIPTION

[0065] The following describes the implementation of the present invention through specific embodiments, and those skilled in the art can easily understand other advantages and effects of the present invention from the contents disclosed in this specification. The present invention can also be implemented or applied through other different specific implementations, and the details in this specification can also be modified or changed in various ways based on different viewpoints and applications without departing from the spirit of the present invention.

[0066] It should be noted that, in the absence of conflict, the features in the following examples and embodiments can be combined with each other. It should also be understood that the terms used in the examples of the present invention are intended to describe specific embodiments rather than to limit the scope of the present invention. The test methods in the following examples that do not specify specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0067] When numerical ranges are given in the embodiments, it should be understood that, unless otherwise specified in the present invention, both endpoints of each numerical range and any value between the two endpoints can be selected. Unless otherwise defined, all technical and scientific terms used in the present invention are familiar to those skilled in the art and the description of the present invention, and any methods, equipment and materials of the prior art similar or equivalent to the methods, equipment and materials described in the embodiments of the present invention can also be used to implement the present invention.

[0068] The present invention is further described below by means of specific examples, but the present invention is not limited thereto, and the specific protection scope is shown in the claims.

[0069] Example 1

[0070] Preparation of vanadium dioxide powder

[0071] 10gV 2 O 5Add to a beaker containing 300 mL of deionized water, heat the dispersion to 65°C, and then drop 5.0 g of hydrazine hydrate (40 wt%) into the dispersion at a rate of 0.5 mL / min under stirring. Continue stirring for 1 hour after the dropwise addition, then transfer the dispersion to a reactor and react at 260°C for 24 hours. After the reaction is completed, centrifuge several times, and the centrifuged product is vacuum dried to obtain vanadium dioxide powder.

[0072] Preparation of PDMA-DOPAT Hydrophilic Polymers by Reversible Addition Fragmentation Chain Transfer (RAFT) Polymerization

[0073] 10.0 g N,N-dimethylacrylamide (DMA), 0.55 g S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT), and 0.04 g azobisisobutyronitrile (AIBN) were added to 30 mL 1,4-dioxane and completely dissolved. The system was stirred and reacted at 65°C for 16 h under nitrogen protection. The resulting solution was precipitated and washed in n-hexane, and the product was filtered off and dried in vacuum at 40°C to obtain trithioester-terminated poly(N,N-dimethylacrylamide) (PDMA-DOPAT) yellow powder.

[0074] Preparation of amphiphilic block polymer PDMA-b-PHFBMA-DOPAT

[0075] 3.0 g PDMA-DOPAT, 2.1 g hexafluorobutyl methacrylate (HFBMA) and 0.02 g AIBN were added into 24 mL tetrahydrofuran (THF) and completely dissolved. The mixture was stirred at 60 °C for 20 h under nitrogen protection. After the reaction, the mixture was precipitated and washed in n-hexane. The solid product was filtered and dried in vacuum at 45 °C to obtain poly(N,N-dimethylacrylamide-b-hexafluorobutyl methacrylate) (PDMA-b-PHFBMA-DOPAT) as a light yellow powder.

[0076] Preparation of Thiol-terminated PDMA-b-PHFBMA-SH

[0077] 3.0 g PDMA-b-PHFBMA-DOPAT, 0.55 g n-hexylamine and 0.065 g tributylphosphine were added to 10 mL tetrahydrofuran, and the mixture was stirred at 25 °C for 8 h under nitrogen protection. After the reaction, the mixture was precipitated in n-hexane and washed three times. The solid product was vacuum dried at 40 °C to obtain PDMA-b-PHFBMA-SH as a white powder.

[0078] VO 2 @KH-570 Preparation of Nanopowder

[0079] 1.0 g VO 2The nanopowder was ultrasonically dispersed in 100 mL of anhydrous ethanol for 40 min, ammonia was added dropwise to adjust the pH to 10, 0.2 g of γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) was added, and then the system was heated to 50 ° C for 8 h. After the reaction, the system was centrifuged and washed with anhydrous ethanol several times to remove the unreacted KH-570. The solid product after centrifugation was vacuum dried at 60 ° C to obtain VO 2 @KH-570 nano powder.

[0080] VO 2 Preparation of @PHFBMA-b-PDMA nanoparticles

[0081] 0.50 g VO 2 @KH-570 nanopowder was dispersed in 20 mL THF by ultrasonic for 30 min, then 0.25 g PDMA-b-PHFBMA-SH was added and fully dissolved, and then 0.02 g AIBN was added and reacted at 60 ° C under nitrogen protection for 24 h. After the reaction was completed, it was centrifuged and washed with THF three times, and finally the washed product was vacuum dried at 40 ° C for 24 h to obtain VO 2 @PHFBMA-b-PDMA nanoparticles.

[0082] Example 2

[0083] Preparation of vanadium dioxide powder

[0084] 10gV 2 O 5 Add to a beaker containing 400 mL of deionized water, heat the dispersion to 70°C, and then drop 6.0 g of hydrazine hydrate (40 wt%) into the dispersion at a rate of 0.5 mL / min under stirring. Continue stirring for 2 h after the dropwise addition, then transfer the dispersion to a reactor and react at 260°C for 22 h. Centrifuge several times after the reaction, and the centrifuged product is vacuum dried to obtain vanadium dioxide powder.

[0085] Preparation of PDMA-DOPAT Hydrophilic Polymers by Reversible Addition Fragmentation Chain Transfer (RAFT) Polymerization

[0086] 8.0 g N,N-dimethylacrylamide (DMA), 0.55 g S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT), and 0.04 g azobisisobutyronitrile (AIBN) were added to 30 mL 1,4-dioxane and completely dissolved. The system was stirred and reacted at 70°C for 12 h under nitrogen protection. The resulting solution was precipitated and washed in n-hexane, and the product was filtered off and dried in vacuum at 50°C to obtain trithioester-terminated poly(N,N-dimethylacrylamide) (PDMA-DOPAT) yellow powder.

[0087] Preparation of amphiphilic block polymer PDMA-b-PHFBMA-DOPAT

[0088] 4.0 g PDMA-DOPAT, 2.0 g hexafluorobutyl methacrylate (HFBMA) and 0.04 g AIBN were added into 30 mL tetrahydrofuran (THF) and completely dissolved. The mixture was stirred at 65 °C for 16 h under nitrogen protection. After the reaction, the mixture was precipitated and washed in n-hexane. The solid product was filtered and dried in vacuum at 55 °C to obtain poly(N,N-dimethylacrylamide-b-hexafluorobutyl methacrylate) (PDMA-b-PHFBMA-DOPAT) as a light yellow powder.

[0089] Preparation of Thiol-terminated PDMA-b-PHFBMA-SH

[0090] 3.0 g PDMA-b-PHFBMA-DOPAT, 0.612 g n-hexylamine and 0.075 g tributylphosphine were added to 15 mL tetrahydrofuran, and the mixture was stirred at 35 °C for 6 h under nitrogen protection. After the reaction, the mixture was precipitated in n-hexane and washed three times. The solid product was vacuum dried at 60 °C to obtain PDMA-b-PHFBMA-SH as a white powder.

[0091] VO 2 @KH-570 Preparation of Nanopowder

[0092] 2.0 g VO 2 The nanopowder was ultrasonically dispersed in 160 mL of anhydrous ethanol for 30 min, ammonia was added dropwise to adjust the pH to 11, 0.3 g of γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) was added, and then the system was heated to 60 ° C for 6 h. After the reaction, the system was centrifuged and washed with anhydrous ethanol several times to remove the unreacted KH-570. The solid product after centrifugation was vacuum dried at 40 ° C to obtain VO 2 @KH-570 nano powder.

[0093] VO 2 Preparation of @PHFBMA-b-PDMA nanoparticles

[0094] 0.70 g VO 2 @KH-570 nanopowder was dispersed in 20 mL THF by ultrasonic for 20 min, then 0.50 g PDMA-b-PHFBMA-SH was added and fully dissolved, and then 0.03 g AIBN was added and reacted at 70 ° C under nitrogen protection for 12 h. After the reaction was completed, it was centrifuged and washed with THF 4 times, and finally the washed product was vacuum dried at 50 ° C for 24 h to obtain VO 2 @PHFBMA-b-PDMA nanoparticles.

[0095] Example 3

[0096] Preparation of vanadium dioxide powder

[0097] 8gV 2 O 5 Add to a beaker containing 350 mL of deionized water, heat the dispersion to 75°C, and then drop 5.5 g of hydrazine hydrate (40 wt%) into the dispersion at a rate of 0.5 mL / min under stirring. Continue stirring for 1 hour after the dropwise addition, then transfer the dispersion to a reactor and react at 280°C for 26 hours. After the reaction is completed, centrifuge several times, and the centrifuged product is vacuum dried to obtain vanadium dioxide powder.

[0098] Preparation of PDMA-DOPAT Hydrophilic Polymers by Reversible Addition Fragmentation Chain Transfer (RAFT) Polymerization

[0099] 8.0 g N,N-dimethylacrylamide (DMA), 0.75 g S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) (DOPAT), and 0.06 g azobisisobutyronitrile (AIBN) were added to 30 mL 1,4-dioxane and completely dissolved. The system was stirred and reacted at 60°C for 20 h under nitrogen protection. The resulting solution was precipitated and washed in n-hexane, and the product was filtered off and dried in vacuum at 55°C to obtain trithioester-terminated poly(N,N-dimethylacrylamide) (PDMA-DOPAT) yellow powder.

[0100] Preparation of amphiphilic block polymer PDMA-b-PHFBMA-DOPAT

[0101] 3.5 g PDMA-DOPAT, 1.8 g hexafluorobutyl methacrylate (HFBMA) and 0.03 g AIBN were added into 20 mL tetrahydrofuran (THF) and completely dissolved. The mixture was stirred at 70 °C for 12 h under nitrogen protection. After the reaction, the mixture was precipitated and washed in n-hexane. The solid product was filtered and dried in vacuum at 60 °C to obtain poly(N,N-dimethylacrylamide-b-hexafluorobutyl methacrylate) (PDMA-b-PHFBMA-DOPAT) as a light yellow powder.

[0102] Preparation of Thiol-terminated PDMA-b-PHFBMA-SH

[0103] 4.0 g PDMA-b-PHFBMA-DOPAT, 0.72 g n-hexylamine and 0.083 g tributylphosphine were added to 20 mL tetrahydrofuran, and the mixture was stirred at 45 °C for 4 h under nitrogen protection. After the reaction, the mixture was precipitated in n-hexane and washed three times to obtain a solid product, which was finally dried in vacuum at 60 °C to obtain PDMA-b-PHFBMA-SH as a white powder.

[0104] VO 2 @KH-570 Preparation of Nanopowder

[0105] 1.0 g VO 2 The nanopowder was ultrasonically dispersed in 150 mL of anhydrous ethanol for 30 min, ammonia was added dropwise to adjust the pH to 12, 0.15 g of γ-(methacryloyloxy)propyltrimethoxysilane (KH-570) was added, and then the system was heated to 45 ° C for 12 h. After the reaction, the system was centrifuged and washed with anhydrous ethanol several times to remove the unreacted KH-570. The solid product after centrifugation was vacuum dried at 50 ° C to obtain VO 2 @KH-570 nano powder.

[0106] VO 2 Preparation of @PHFBMA-b-PDMA nanoparticles

[0107] 0.50 g VO 2 @KH-570 nanopowder was dispersed in 30 mL THF by ultrasonic for 40 min, then 0.15 g PDMA-b-PHFBMA-SH was added and fully dissolved, and then 0.02 g AIBN was added and reacted at 65 ° C under nitrogen protection for 18 h. After the reaction was completed, it was first centrifuged and then washed with THF three times. Finally, the washed product was vacuum dried at 60 ° C for 24 h to obtain VO 2 @PHFBMA-b-PDMA nanoparticles.

[0108] Application Example 1

[0109] 1 g VO prepared in Example 2 2 The powder was evenly dispersed in 99 mL of distilled water and ultrasonicated for 30 min using a cell crusher until the powder was evenly dispersed to prepare VO 2 Base slurry. Take 7.5g of waterborne polyurethane resin (model: Shengbang 9080) in a beaker, take 5g of the above slurry and add it to the waterborne resin at a speed of 0.8mL / min and stir until it is evenly dispersed. Weigh 2.5g of film-forming aid, 0.3g of leveling agent, and 0.3g of defoaming agent in a 10mL serum bottle, mix well, and slowly add it to the beaker. After fully stirring, VO 2 Based on intelligent thermal insulation coating.

[0110] Application Example 2

[0111] 1 g of VO prepared in Example 3 2 @KH-570 nanopowder was evenly dispersed in 99 mL of water solvent and ultrasonicated with a cell crusher for 40 min until the powder was evenly dispersed to prepare VO 2@KH-570 based slurry. Take 7.5g of waterborne polyurethane resin (model: Shengbang 9080) in a 20mL beaker, take 4g of the above slurry and add it to the waterborne resin at a speed of 1.2mL / min and stir until it is evenly dispersed. Weigh 2.5g of film-forming aid, 0.3g of leveling agent, and 0.3g of defoaming agent in a 10mL serum bottle, mix well, and slowly add it to the beaker. After fully stirring, VO 2 @KH-570 based intelligent thermal insulation coating.

[0112] Application Example 3

[0113] VO 2 Preparation of highly weather-resistant water-based intelligent thermal insulation coating based on @PHFBMA-b-PDMA nanoparticles

[0114] 1 g of VO prepared in Example 1 2 @PHFBMA-b-PDMA nanoparticles were evenly dispersed in 99 mL of water solvent and ultrasonicated for 30 min by a cell crusher until the powder was evenly dispersed to prepare VO 2 @PHFBMA-b-PDMA based slurry. Take 7.5g of waterborne polyurethane resin (model: Shengbang 9080) in a 20mL beaker, take 7g of the above slurry and add it to the waterborne resin at a speed of 1.8mL / min and stir until it is evenly dispersed. Weigh 2.5g of film-forming aid, 0.3g of leveling agent, and 0.3g of defoaming agent in a 10mL serum bottle, mix well, and slowly add it to the beaker. After fully stirring, VO 2 @PHFBMA-b-PDMA based smart thermal insulation coating.

[0115] Preparation of smart thermal insulation coating

[0116] Take 4 mL of VO prepared in Examples 1 to 3 respectively. 2 Based on intelligent thermal insulation coating, VO 2 @KH-570 based intelligent thermal insulation coating, VO 2 The PHFBMA-b-PDMA-based smart thermal insulation coating was evenly coated on a glass substrate using a 50 μm thick wire rod by roller coating, and then the substrate was quickly placed in a 60°C oven to accelerate the evaporation of the solvent to obtain VO 2 , VO 2 @KH570、VO 2 @PHFBMA-b-PDMA-based smart thermal insulation coating, the dry film thickness is about 5μm after thorough drying.

[0117] Performance Characterization

[0118] 1. Figure 1Figure 1 is a schematic diagram of the synthesis reaction of PDMA-b-PHFBMA-DOPAT block polymer. It can be seen from the figure that the synthesis of thiol-terminated PDMA-b-PHFBMA-SH block polymer is mainly divided into three steps. First, DMA is used as a monomer and DOPAT is used as a chain transfer agent to prepare a PDMA-DOPAT homopolymer. Subsequently, the PDMA-DOPAT homopolymer is used as a macromolecular chain transfer agent and further polymerized with the HFBMA monomer to prepare a PDMA-b-PHFBMA-DOPAT amphiphilic block polymer with a trithioester group at the end group. Finally, the trithioester group is converted into a thiol group through an aminolysis reaction to prepare a PDMA-b-PHFBMA-SH block polymer.

[0119] 2. The PDMA-b-PHFBMA-DOPAT block polymer prepared in Example 1 was dissolved in deuterated dimethyl sulfoxide solvent and tested by H NMR spectrum using Avance III HD 600 MHz NMR instrument. The results are as follows: Figure 2 As shown, from Figure 2 It can be seen that 0.8ppm belongs to -CH 3 , 1.42-1.91ppm is attributed to the main chain -CH 2 -, 2.30-2.78ppm belong to the characteristic peak of the main chain -CH-. At the same time, PDMA-b-PHFBMA-DOPAT showed a characteristic proton signal of the methyl group in the RAFT agent at 0.95ppm, indicating that the polymer product retained the functional group of DOPAT, and the PDMA-b-PHFBMA-DOPAT block polymer was successfully prepared.

[0120] 3. PDMA-b-PHFBMA-DOPAT and PDMA-b-PHFBMA-SH prepared in Example 1 were respectively prepared into polymer solutions with a concentration of 0.001 g / mL using tetrahydrofuran as solvent, and UV absorption tests were performed using a UV-3600 UV-visible-near infrared spectrophotometer. The results are as follows: Figure 3 As shown. Figure 3 It can be seen that before aminolysis, the PDMA-b-PHFBMA-DOPAT block polymer showed an ultraviolet absorption peak of the trithioester group at 308nm, proving that the polymer chain segment contained DOPAT chain transfer agent, and after the aminolysis reaction, the absorption peak of the polymer at 308nm disappeared, proving that the trithioester group in the block polymer disappeared, and the trithioester group was successfully converted into a thiol group to prepare the PDMA-b-PHFBMA-SH block polymer.

[0121] 4. The vanadium dioxide powder prepared in Example 1 was characterized by using a Gemini 300 scanning electron microscope. Figure 4As shown, it can be seen that the obtained vanadium dioxide powder has a smaller primary particle size (30-40 nm) and there is no obvious agglomeration between the particles.

[0122] 5. Take the vanadium dioxide powder and VO2 prepared in Example 1 respectively. 2 @PHFBMA-b-PDMA nanoparticles were tested by XRD at room temperature using a SmartlabSE powder diffractometer. The test range was 10-80° and the test step was 1° / min. The crystal form changes of the two were observed. The results are as follows Figure 5 As shown, from Figure 5 It can be seen that the powders before and after modification are monoclinic phase, indicating that the polymer modified VO 2 The powder process will not affect the crystal shape and dimming performance of the powder.

[0123] 6. Take the vanadium dioxide powder and VO2 prepared in Example 1 respectively. 2 @KH-570 nano powder, VO 2 @PHFBMA-b-PDMA nanoparticles were analyzed by TGA55 thermogravimetric analyzer. 2 The sample was tested for thermal weight loss in the atmosphere, the test temperature range was 30~800℃, the heating rate was 10℃ / min, and the results were as follows Figure 6 As shown, from Figure 6 It can be seen that VO 2 Nano powders hardly decompose and lose weight at 700℃, and have good thermal stability. 2 When the temperature of the hybrid particles was raised to 700°C, the powder lost about 2.8% of its weight, proving that KH-570 was successfully grafted onto the powder surface and the grafting amount was about 2.8%. 2 @PHFBMA-b-PDMA nanoparticles, whose thermal weight loss at 700°C was about 13.9%, indicating that the block polymer was successfully grafted onto the powder surface through the click reaction.

[0124] 7. Take the vanadium dioxide powder and VO2 prepared in Example 1 respectively. 2 0.1 g of each PDMA nanoparticle was dispersed in 8 mL of distilled water, and then ultrasonically dispersed in a cell crusher for 30 min. The sedimentation of the two was observed. The results are as follows Figure 7 As shown, from Figure 7 It can be seen that on the 4th day, VO 2 The powder has already settled significantly, and VO 2 @KH-570 and VO 2 @PHFBMA-b-PDMA powder still maintains good dispersibility, and after standing for 5 days, VO 2@KH-570 also began to partially settle. The main reason was that although the hydroxyl groups after hydrolysis of the silane coupling agent could increase the VO 2 The dispersion of VO in water is good, but the small organic molecules in the coupling agent are hydrophobic, so as the standing time increases, 2 @KH-570 will also settle. After 7 days of standing, VO 2 @PHFBMA-b-PDMA powder still maintains a good dispersion state, indicating that VO 2 @PHFBMA-b-PDMA powder exhibits excellent dispersion effect in aqueous system, which is mainly attributed to the fact that the outermost PDMA hydrophilic block can remain stretched in water, allowing the powder to maintain good suspension stability in the aqueous phase.

[0125] 8. Take the VO obtained in Example 1 2 Powder, VO 2 @KH-570 and VO 2 0.1 g of each PHFBMA-b-PDMA nanoparticle was dispersed in 0.5 mol / L H 2 SO 4 The acid resistance test was carried out by ultrasonic dispersion in the solution for 30 min, and the color change of the dispersion was observed; 0.1 g VO 2 Powder, VO 2 @KH-570 and VO 2 @PHFBMA-b-PDMA nanoparticles were dispersed in 0.5 mol / L H 2 O 2 The anti-oxidation test was carried out by ultrasonic dispersion in the solution for 30 minutes to observe the oxidation of the powder; the results are as follows Figure 8 As shown, Figure 8 (a) is the test result of powder acid resistance, (b) is the test result of powder oxidation resistance (from left to right: VO 2 , VO 2 @KH-570, VO 2 @PHFBMA-b-PDMA).

[0126] In the powder acid resistance test ( Figure 8 (a)), VO 2 The nanopowder was quickly corroded by acid and the decomposed solution turned blue. This was mainly due to the unmodified VO 2 The powder will be directly dissolved by dilute sulfuric acid to produce blue VO 2+ ions. And VO 2 @KH-570 dispersion began to turn light blue after standing for 2 days, while VO 2@PHFBMA-b-PDMA dispersion remained well dispersed and had no color change on the 5th day, indicating that the powder modified with block polymer had the best acid resistance.

[0127] In the powder antioxidant test ( Figure 8 (b)) It was observed that the unmodified VO 2 The dispersion quickly turned into a brown solution due to the 2 After oxidation, it produces brown [V 4 O 9 ] 2- 、[VO 4 ] 4- ions, indicating that the unmodified vanadium dioxide has the worst stability. 2 @KH-570 dispersion showed no color change after 2 days of standing. When the standing time was extended to 5 days, VO 2 @KH-570 dispersion begins to turn yellow, and VO 2 @PHFBMA-b-PDMA dispersion still maintains a good dispersion state and no color change, indicating that the powder modified by the block polymer exhibits excellent antioxidant properties and improves the stability of the powder.

[0128] 9. Fig. 9 The following are the actual pictures of the thermal insulation coatings prepared in Application Example 1, Application Example 2, and Application Example 3. It can be seen from the pictures that they are all brown-yellow with excellent light transmittance, and the surface of the film coating is uniform. The optical properties of the three different thermal insulation coatings were tested at 20℃ and 90℃ respectively using an ultraviolet-visible-near infrared spectrophotometer (UV), with a test wavelength range of 250-2500nm. The results are as follows: Fig. 9 As shown in (d), it can be seen from the figure that the film has excellent solar modulation ability when tested at high temperature 90℃ and low temperature 20℃, where the calculated VO 2 Film's solar modulation capability ΔT sol =8.28%, VO 2 @KH-570 film's solar light modulation capability ΔT sol =9.82%, and VO 2 The solar light modulation capability of @PHFBMA-b-PDMA film increases to ΔT sol =10.84%, indicating that the modification of block polymer is beneficial to improving the dimming performance of the film. This is because the hydrophilic PDMA chain segment of the outermost layer of the powder improves the dispersibility of the inorganic powder and reduces the agglomeration of large powder particles, while the fluorinated PHFBMA in the inner layer improves the stability of the powder, ultimately making the VO coated by the block polymer 2 The nanoparticles exhibit optimal dimming performance and can achieve efficient near-infrared light regulation capabilities.

[0129] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.

Claims

1. A method for preparing VO2@PHFBMA-b-PDMA nanoparticles, characterized in that: The following steps are involved: (1) Preparation of vanadium dioxide powder: Add V2O5 to deionized water, stir to form a dispersion, heat the dispersion and drop hydrazine hydrate under stirring, continue stirring to react after the dropwise addition is completed, then transfer the solution to a reactor to continue the reaction, perform post-treatment after the reaction is completed, and obtain vanadium dioxide powder; (2) Preparation of thiol-terminated PDMA-b-PHFBMA-SH amphiphilic block polymer: a) adding N,N-dimethylacrylamide, S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) and azobisisobutyronitrile to 1,4-dioxane solvent, stirring and reacting under nitrogen protection after being completely dissolved, precipitating and washing the resulting solution in n-hexane after the reaction, and filtering the resulting product under vacuum drying at 30-60° C. for 8-24 h to obtain trithioester-terminated poly(N,N-dimethylacrylamide), which is recorded as PDMA-DOPAT; b) adding the PDMA-DOPAT, hexafluorobutyl methacrylate and azobisisobutyronitrile prepared in step a) into tetrahydrofuran, stirring until completely dissolved, stirring and reacting under nitrogen protection, and after the reaction, dropping the solution into n-hexane for precipitation and washing, filtering and collecting the precipitate, and vacuum drying at 30-60° C. for 8-24 h to obtain poly(N,N-dimethylacrylamide-b-hexafluorobutyl methacrylate), recorded as PDMA-b-PHFBMA-DOPAT; c) adding the PDMA-b-PHFBMA-DOPAT, n-hexylamine and tributylphosphine prepared in step b) into tetrahydrofuran, stirring and reacting under nitrogen protection, adding the reaction solution into n-hexane for precipitation and washing to obtain a solid product after the reaction is completed, and vacuum drying at 30-60° C. for 8-24 hours to obtain a thiol-terminated PDMA-b-PHFBMA-SH amphiphilic block polymer; (3) Preparation of VO2@PHFBMA-b-PDMA nanoparticles: a) ultrasonically dispersing the vanadium dioxide powder prepared in step (1) in anhydrous ethanol, adding ammonia water to adjust the pH, adding γ-(methacryloyloxy)propyltrimethoxysilane, and then heating the system for reaction. After the reaction, centrifuging, washing with anhydrous ethanol, and vacuum drying at 30-60° C. for 12-24 h to obtain VO2@KH-570 nanopowder; b) Ultra-dispersing VO2@KH-570 nanopowder in tetrahydrofuran, then adding the PDMA-b-PHFBMA-SH amphiphilic block polymer prepared in step (2), stirring until fully dissolved, then adding initiator AIBN, and then reacting under nitrogen protection. After the reaction is completed, centrifuging and washing with tetrahydrofuran, the washed product is vacuum dried at 30-60° C. for 12-24 h to obtain VO2@PHFBMA-b-PDMA nanoparticles.

2. The method according to claim 1, characterized in that It also includes one or more of the following technical features: In step (1), the mass ratio of V2O5 to deionized water is (1-7): (60-160); The mass ratio of V2O5 to hydrazine hydrate in step (1) is (5-10): (1-5).

3. The method according to claim 1, characterized in that It also includes one or more of the following technical features: In step (2), the mass ratio of N,N-dimethylacrylamide and S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) in a) is (80-120):(5-15); In step (2), the mass ratio of S-1-dodecyl-S′-(α,α′-dimethyl-α″-propionic acid) and azobisisobutyronitrile in a) is (15-50):(0.5-7); In step (2), the mass ratio of 1,4-dioxane to N,N-dimethylacrylamide in a) is (5-10): (0.5-5); In step (2), the mass ratio of PDMA-DOPAT, hexafluorobutyl methacrylate and azobisisobutyronitrile in b) is (260-350): (150-240): (0.5-5); In step (2), the mass ratio of PDMA-DOPAT to tetrahydrofuran in b) is 1:(3-20); In step (2), the mass ratio of PDMA-b-PHFBMA-DOPAT, n-hexylamine and tributylphosphine in c) is (250-450):(45-90):(2-12).

4. The method according to claim 1, characterized in that It also includes one or more of the following technical features: In step (3), the mass ratio of vanadium dioxide powder to anhydrous ethanol in a) is (0.1-4): (60-120); In step (3), the mass ratio of vanadium dioxide powder to γ-(methacryloyloxy)propyltrimethoxysilane in a) is (5-30):(0.5-3); In step (3), the mass ratio of VO2@KH-570 nanopowder to tetrahydrofuran in b) is (0.1-10):(60-120).

5. VO2@PHFBMA-b-PDMA nanoparticles prepared by the method according to any one of claims 1 to 4, characterized in that: The particle size of the VO2@PHFBMA-b-PDMA nanoparticles is 30-40 nm.

6. An intelligent thermal insulation coating prepared by using VO2@PHFBMA-b-PDMA nanoparticles prepared by the method according to any one of claims 1 to 4, characterized in that: The preparation method is as follows: uniformly add the aqueous dispersion of VO2@PHFBMA-b-PDMA nanoparticles into the aqueous resin, stir until uniformly dispersed, and obtain the system dispersion; uniformly mix the film-forming aid, leveling agent, and defoaming agent, and then add them to the system dispersion, stir evenly, and obtain the smart thermal insulation coating.

7. The intelligent thermal insulation coating according to claim 6, characterized in that: The mass ratio of the aqueous resin to the aqueous dispersion of VO2@PHFBMA-b-PDMA nanoparticles is (50-100):(40-60); the mass percentage of the aqueous dispersion of VO2@PHFBMA-b-PDMA nanoparticles is 1wt%.

8. The intelligent thermal insulation coating according to claim 6, characterized in that: The dropping speed of the aqueous dispersion of VO2@PHFBMA-b-PDMA nanoparticles is 0.5 to 2 mL / min.

Citation Information

Patent Citations

  • Polyacrylate polymer-vanadium dioxide microcapsule as well as preparation method and application thereof

    CN114367250A

  • Modified vanadium dioxide dispersion as well as preparation method and application thereof

    CN114369321A